Role of Notary Waarmerking Investment Agreements - Tarjono Tarjono (Sultan Agung Notary Law Review, 2020)
The objectives of this study are to: 1) To determine the role of the notary in mewaarmerking of the agreement deed in a legal certainty investment case study of PT Cakrabuana Sukses Indonesia (CSI). 2) To find out the weaknesses and solutions to the notary's role in merging investment agreement deeds with legal certainty as a case study of PT Cakrabuana Sukses Indonesia (CSI). The approach method in this research is the normative juridical approach, or literature law research, namely legal research which is carried out by examining library materials or secondary data. In this case by examining the problems in terms of Act No. 2 of 2014 concerning Amendments to Act No. 30 of 2004 concerning the Position of Notary Public. Based on the results of data analysis, it is concluded that: 1) Article 1 number 1 of Act No. 2 of 2014 concerning Amendments to Act No. 30 of 2004 concerning the Position of Notary states that Notaries are public officials who are authorized to make authentic deeds as long as the making of certain authentic deeds is not specific to other public officials. In other words, the notary has the authority in all deeds to the extent that it is within its authority. Furthermore, in Article 15 paragraph (2) letter b of Act No. 2 of 2014 concerning Amendments to Act No. 30 of 2004 concerning Notary Position, it is stated that notaries are also authorized to post letters under their hands by registering in a special book. The authority is a limitation, that the notary does not take an action outside his / her authority. However, in practice, there are weaknesses in the notary, 2) The weakness of the notary's role in making the investment agreement deed that has been made between PT Cakrabuana Sukses Indonesia (CSI) and its customers is that the notary is unable to ensure the legality of PT Cakrabuana Sukses Indonesia (not registered with the Financial Services Authority) and the form of investment agreement that has been made is the investment agreement below hand where the authority of the notary is only to put the letter under the hand so that the role of the notary does not exist.